2021
DOI: 10.1002/pi.6335
|View full text |Cite
|
Sign up to set email alerts
|

Alkene polymerization reactions with catalysts based on acetylacetonate complexes of vanadium and titanium: effect of cocatalyst

Abstract: Alkene polymerization reactions were studied with three catalyst systems containing complexes of vanadium and titanium with the acetylacetonate ligand (V(acac)3, VO(acac)2, Ti(acac)2Cl2) and a binary activator, a combination of Al(C2H5)2Cl and Mg(C4H9)2 at an [Al]:[Mg] molar ratio of ca 3. All three catalysts are highly active in ethylene homopolymerization reactions. They copolymerize ethylene and 1‐hexene to random, compositionally uniform products with 1‐hexene content of up to 20–25%. The Ti(acac)2Cl2–Al(C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Our earlier research showed that combinations of two types of organometallic compounds, AlR 2 Cl (R = CH 3 , C 2 H 5 , i-C 4 H 9 ) and MgR 0 2 (R 0 = n-and i-C 4 H 9 ), at an [Al]/[Mg] molar ratio of over 2 are universal activators for various types of transition metal polymerization catalysts, including TiCl 4 , 37,38 Ti 3+ -and Ti 4+ -based heterogeneous and supported catalysts, 39 Ti(OR) 4 , 22,40 metallocene complexes 41 and numerous pre-and post-metallocene catalysts. 39,[41][42][43][44][45] The Ti(Oi-C 3 H 7 ) 4 -Al(C 2 H 5 ) 2 Cl/Mg(C 4 H 9 ) 2 catalyst used in this research is a pseudo-homogeneous catalytic system. All its components are soluble in aliphatic and aromatic hydrocarbons but combining Al(C 2 H 5 ) 2 Cl and Mg(C 4 H 9 ) 2 generates finely dispersed MgCl 2 crystals with a Lewis-acidic surface: [37][38][39]46 Mg C…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier research showed that combinations of two types of organometallic compounds, AlR 2 Cl (R = CH 3 , C 2 H 5 , i-C 4 H 9 ) and MgR 0 2 (R 0 = n-and i-C 4 H 9 ), at an [Al]/[Mg] molar ratio of over 2 are universal activators for various types of transition metal polymerization catalysts, including TiCl 4 , 37,38 Ti 3+ -and Ti 4+ -based heterogeneous and supported catalysts, 39 Ti(OR) 4 , 22,40 metallocene complexes 41 and numerous pre-and post-metallocene catalysts. 39,[41][42][43][44][45] The Ti(Oi-C 3 H 7 ) 4 -Al(C 2 H 5 ) 2 Cl/Mg(C 4 H 9 ) 2 catalyst used in this research is a pseudo-homogeneous catalytic system. All its components are soluble in aliphatic and aromatic hydrocarbons but combining Al(C 2 H 5 ) 2 Cl and Mg(C 4 H 9 ) 2 generates finely dispersed MgCl 2 crystals with a Lewis-acidic surface: [37][38][39]46 Mg C…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier research showed that combinations of two types of organometallic compounds, AlR 2 Cl (R = CH 3 , C 2 H 5 , i ‐C 4 H 9 ) and MgR′ 2 ( R ′ = n ‐ and i ‐C 4 H 9 ), at an [Al]/[Mg] molar ratio of over 2 are universal activators for various types of transition metal polymerization catalysts, including TiCl 4 , 37, 38 Ti 3+ ‐ and Ti 4+ ‐based heterogeneous and supported catalysts, 39 Ti(OR) 4 , 22, 40 metallocene complexes 41 and numerous pre‐ and post‐metallocene catalysts 39, 41–45 …”
Section: Discussionmentioning
confidence: 99%